Flint Kill Creek : stories of mystery and suspense - Oates, Joyce Carol, 1938- (The Mysterious Press, 2024)
"These new, recent, and reformulated stories by Joyce Carol Oates, collected here for the first time, showcase a wide range of crime fiction and psychological suspense. A young, insecure woman finds her relationship changing as she grows more and more dependent on a man who likes to take her on long walks beside a dangerously roaring creek. Another woman, nervous around men, not quite knowing how to act when paid a compliment, becomes flustered when a doctor suggests they go out for coffee, or possibly a drink. She finally decides that she will join him when he suggests they meet at his home. A man is so forgetful that his wife panics and yells into his phone, asking where their daughter has gone. A young man is curious to see why sirens have filled the night and the police arrest him, beginning an unimaginable nightmare. A woman resents that a colleague has achieved greater success and thinks she ought to do something about it. It is impossible to know where a story by the creative genius of Joyce Carol Oates will end and what frightening paths will lead to that end"--